Composiciones de betalaína sólidas y métodos - PIETRZKOWSKI, Zbigniew; THRESHER, Wayne Carl (2021)
Una composición sólida que comprende al menos diez betalaínas químicamente distintas con una concentración total de betalaína de al menos un 5 % en peso y una proporción de betalaína con respecto a azúcar de al menos 0,3, en donde la composición es un sólido de flujo libre en forma de polvo que es al menos un 90 % soluble cuando se disuelve en agua con una concentración de al menos 50 mg/ml. Solid, free-flowing, and substantially completely dissolvable preparations with high betalain content are presented. Most typically, the betalain profile of the preparations is near natural and includes betalains in an amount of between 10-40 wt %. As the preparations of the inventive subject matter maintain chemical stability and flowability over extended periods of time, it should be noted that the betalain preparations are now amenable to compounding in small and measured quantities. Furthermore, new biological activities of betalains are shown, and especially include significant induction of SIRT and reduction of serum triglyceride.